NOAEL-dose of a neonicotinoid pesticide, clothianidin, acutely induce anxiety-related behavior with human-audible vocalizations in male mice in a novel environment. (5th January 2018) - Hirano, Tetsushi; Yanai, Shogo; Takada, Tadashi; Yoneda, Naoki; Omotehara, Takuya; Kubota, Naoto; Minami, Kiichi; Yamamoto, Anzu; Mantani, Youhei; Yokoyama, Toshifumi; Kitagawa, Hiroshi; Hoshi, Nobuhiko
Highlights: Neurobehavioral effects of acute clothianidin, one of neonicotinoid pesticides, were investigated in mice. Clothianidin induced human-audible vocalizations and anxiety-like behavior in mice in elevated plus maze test. Neuroactivities in parts of thalamic and hippocampal regions were increased in clothianidin-administrated mice. These results indicated that clothianidin affects stress reactivity in a novel environment. Abstract: Neonicotinoids are novel systemic pesticides acting as agonists on the nicotinic acetylcholine receptors (nAChRs) of insects. Experimental studies have revealed that neonicotinoids pose potential risks for the nervous systems of non-target species, but the brain regions responsible for their behavioral effects remain incompletely understood. This study aimed to assess the neurobehavioral effects of clothianidin (CTD), a later neonicotinoid developed in 2001 and widely used worldwide, and to explore the target regions of neonicotinoids in the mammalian brain. A single-administration of 5 or 50 mg/kg CTD to male C57BL/6N mice at or below the no-observed-adverse-effect level (NOAEL) induced an acute increase in anxiety during the elevated plus-maze test. In addition, mice in the CTD-administered group spontaneously emitted human-audible vocalizations (4–16 kHz), which are behavioral signs of aversive emotions, and showed increased numbers of c-fos immunoreactive cells in the paraventricular thalamic nucleus and dentate gyrus of the hippocampus. In conclusion, mice exposed to NOAEL-dose CTD would be rendered vulnerable to a novel environment via the activation of thalamic and hippocampal regions related to stress responses. These findings should provide critical insight into the neurobehavioral effects of neonicotinoids on mammals.